Functioning in an Illness and Quality of Life versus the Prevalence of Depression and Anxiety Disorders in Patients with High Cardiovascular Risk - Piotr Michalski; Agata Kosobucka-Ozdoba; Łukasz Pietrzykowski; Michał Kasprzak; Klaudyna Grzelakowska; Alicja Rzepka-Cholasińska; Aldona Kubica (MDPI AG, 2024)
Background: A chronic disease occurring in a person's life is a stressor, disrupting every aspect of their life. Objectives: This study aims to assess the relationship between functioning in chronic illness and quality of life with the prevalence of symptoms of depression and anxiety in patients with high cardiovascular risk. Material and methods: This study included 200 patients (aged 18-80 years) under the care of a primary care physician, diagnosed with hypertension and/or hypercholesterolemia, and/or diabetes between 6 and 24 months before the enrollment. The presented analysis assessed the symptoms of anxiety and depression using the Hospital Anxiety and Depression Scale (HADS); and the quality of life of patients with cardiovascular disease using the Heart Quality of Life (HeartQoL) questionnaire and functioning in chronic illness using the Functioning in Chronic Illness Scale (FCIS). Results: The HADS scores amounted to 4.34 ± 3.414 points for the HADS-Anxiety subscale and 3.20 ± 2.979 points for the HADS-Depression subscale. The score indicative of functioning in chronic illness assessed with the FCIS was 98.32 ± 13.89 points. The independent predictors of HADS-anxiety were HeartQoL Emotional and FCIS Global, while HeartQoL Global and FCIS Global were the independent predictors for HADS-depression. Better functioning in chronic illness (FCIS Global) was associated with less frequent symptoms of anxiety and depression based on the HADS: HADS-Anxiety (R Spearmann = −0.3969; p < 0.0001) and HADS-Depression (R Spearmann = −0.5884; p < 0.0001). Higher HeartQoL scores, both globally, as well as in emotional and physical dimensions, were associated with a lower severity of anxiety and depression assessed with the HADS: HADS-Anxiety (R Spearmann = −0.2909; p = 0.0001) and HADS-Depression (R Spearmann = −0.2583; p = 0.0002). Conclusions: The quality of life and functioning in chronic illness are connected with symptoms of depression and anxiety. When assessing the severity of the depression symptoms in relation to the individual aspects of functioning in chronic illness, the areas requiring supportive-educational intervention can be identified. The assessment of both functioning in a chronic disease and the severity of the depression symptoms should be included in a standard nursing diagnosis and further supportive and educational intervention.